2012
DOI: 10.1002/mrd.22024
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of RNA‐binding proteins regulates cell function and differentiation

Abstract: Arginine methylation is a post-translational modification that regulates protein function. RNA-binding proteins are an important class of cell function mediators, some of which are methylated on arginine. Early studies of RNA-binding proteins and arginine methylation are briefly introduced, and the enzymes that mediate this post-translational modification are described. We review the most common RNA-binding domains and briefly discuss how they associate with RNAs. We address the following groups of RNA-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 155 publications
6
78
0
Order By: Relevance
“…7D, lanes 8 to 11 and 13). The latter observation confirms our previous finding that the combinatorial change of arginines 22,23,25, and 26 to alanine changes pUL69 into a UAP56-binding-deficient mutant (6,8,9). Interestingly, however, the arginines at positions 28 and 29 were not required for UAP56 interaction, since a mutant harboring the respective substitutions was coprecipitated by Myc-UAP56 (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…7D, lanes 8 to 11 and 13). The latter observation confirms our previous finding that the combinatorial change of arginines 22,23,25, and 26 to alanine changes pUL69 into a UAP56-binding-deficient mutant (6,8,9). Interestingly, however, the arginines at positions 28 and 29 were not required for UAP56 interaction, since a mutant harboring the respective substitutions was coprecipitated by Myc-UAP56 (Fig.…”
Section: Resultssupporting
confidence: 80%
“…As suggested by the varying amino acid sequences and different subcellular localizations, PRMTs have distinct substrate specificities (22). In contrast to PMKTs, which mainly modify histones, PRMTs predominantly target nonhistone substrates, for instance, transcription factors, various RNAprocessing factors like hnRNPs, spliceosomal Sm proteins, the DEAD box helicase VASA, and RNA-binding proteins involved in neuronal development, such as FMRP, HuR, and HuD (23). Importantly, arginine methylation was demonstrated to modulate the nucleocytoplasmic transport and the activity of various RNAprocessing factors (24)(25)(26)(27)(28).…”
Section: Importancementioning
confidence: 99%
“…In addition, FMRP has been shown to undergo two post-translational modifications: phosphorylation and arginine methylation , Stetler et al 2006. It has been suggested that phosphorylation might modulate FMRP properties such as association with actively translating polyribosomes and with Dicer (Ceman et al 2003, Cheever & Ceman 2009) while methylation affects both its protein-protein and protein-RNA interactions (Denman 2002, Dolzhanskaya et al 2006, Stetler et al 2006, Blackwell et al 2010, Blackwell & Ceman 2012. The presence of a nuclear localization signal and a nuclear export signal suggests shuttling between the nucleus and the cytoplasm (Eberhart et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Arginine methylation is an important post-translational modification that may occur as symmetrical dimethylarginines (sDMAs), asymmetrical dimethylarginines (aDMAs), or monomethylarginines (Krause et al 2007;Bedford and Clarke 2009;Blackwell and Ceman 2012). sDMAs occur in "sDMA motifs" composed of multiple arginine-glycine (RG) and arginine-alanine (RA) repeats in various proteins, and modulate diverse cellular processes.…”
Section: Introductionmentioning
confidence: 99%